Experimental and theoretical study of the effect of the particle size of limestone fillers on the rheology of self-compacting concrete. (March 2017) - Benjeddou, Omrane; Soussi, Chokri; Jedidi, Malek; Benali, Mohamed
Abstract: The formulation of self-compacting concrete (SCC) requires a large volume of additions to increase the volume of the paste and reduce the amount of cement. This paper presents the results of an experimental and theoretical study of the effect of particle size of limestone filler on the rheology of SCC in its fresh state. The first part is devoted to the experimental study of the influence of particle size of the limestone filler on the rheology of SCC in the fresh state. In the second part, a simple theoretical model was developed to determine the dosage of filler considering its particle size. Finally, the theoretical model was validated by experimental tests on differents SCC mixed with different quantities of filler predicted by the model. The results showed that all concretes have a similiar rheology and compressive strength. Highlights: The effect of particle size of limestone filler on the properties of SCC in its fresh state. A theoretical model was developed to determine the dosage of filler considering its size. An increase in the fineness of the filler affects self-compacting behavior of the SCC. The effect of particle size has been solved by the development of equivalence model.